Biological and Psychosocial Factors, Risk Behaviors, and Perinatal Asphyxia in a University Hospital: Matched Case–Control Study, Cali, Colombia (2012–2014) - Torres-Muñoz, Javier; Fonseca-Perez, Javier Enrique; Laurent, Katherine (Frontiers in Public Health, 2021)
Introduction. Perinatal asphyxia is one of the main causes of morbidity and mortality in newborns. It generates high costs, both social and economic, and presents modifiable risk factors. Objective. To determine the biological and psychosocial factors and risk behaviors associated with the development of perinatal asphyxia (Sarnat II-III) in newborns from low socioeconomic status, in a tier III university hospital in the city of Cali, Colombia. Materials and Methods. With a case and control design, 216 patients were studied (54 cases/162 controls) (1 case/3 matched controls). The cases were defined as newborns with modified or severe perinatal asphyxia (Sarnat II-III) between 2012 and 2014, with gestational age ≥36 weeks, with neurological signs not attributable to other causes, multi-organ compromise, advanced reanimation, and presence of a sentinel event. For the analysis, conditional logistic regression models were developed to evaluate association (OR), considering that the cases and controls had been paired by the birth and gestational age variables. Results. The final model showed that, from the group of biological variables, meconium amniotic fluid was identified as a risk factor (OR 15.28 95%CI, 2.78 - 83.94). It was also found that induction of labor decreased by 97% (OR 0.03, 95%CI 0.01 - 0.21); monitoring of fetal heart rate decreased by 99% (OR 0.01 95%CI 0.00 - 0.31) the opportunity to develop asphyxia in the newborn. Regarding social variables, lack of social support was identified as a risk factor to develop perinatal asphyxia (OR 6.44 95%CI 1.16 - 35.66); in contrast, secondary school level of education reduced by 85% the probability to develop perinatal asphyxia, compared with pregnant women who only had primary school education (OR 0.15 95%CI 0.03-0.77). Conclusion. Assessment of biological and psychosocial factors and risk behaviors is important in pregnant women to determine the risk of developing perinatal asphyxia in a low-income population.